The Effect of Return on Assets, Company Size and Financial Leverage on Smoothing Measures (Empirical Study on State-Owned Construction Companies Listed in The Jakarta Islamic Index for The 2015-2018 Period) - Ari Kristin Prasetyoningrum; Vanila Hapsari; Dessy Noor Farida (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
The Indonesian government announces that Indonesia will have a new National Capital, one of it’s aims is to smooth the people's economy. Many companies in the construction sector owned by BUMN have long been listed on the Sharia stock exchange. With the existence of this mega project, the recording of profits of go-public companies as well as government-owned companies will receive special attention related to the recording of profits in several previous periods. However, investors must be observant regarding the possibility of companies taking income smoothing actions, some of which are through Return On Assets, Size of the Company and Financial Leverage. The object of research is BUMN construction companies listed in the Jakarta Islamic Index (JII) from 2015 to 2018. The samples used 3 companies based on purposive sampling. Hypothesis testing uses multiple linear regression to test the effect of Return On Assets, Size of the Company and Financial Leverage on Income Smoothing actions by calculating Income Smoothing using the Eckel Index, the analysis technique used is linear regression and the hypothesis testing tool is SPSS 16. The results showed that Return On Assets and Size of the Company had no effect on income smoothing. Meanwhile, Financial Leverage affects income smoothing. Keywords: Return On Asset, Size of The Company, Financial Leverage, Income Smoothing.